A New Method for Solving Quadratic Fractional Programing Problems - Mediya B. Mrakhan; Basiya K.Abdulrahim; Rzgar F. Mahmood; Aram Bajalan; Shwan Adnan Ali (Tikrit Journal of Pure Science)
In this article, the given algorithms were expanded and a methodology was developed to solve an objective function of a quadratic fractional programming problem (QFPP) with linear constraints. A new method called RBM was introduced to directly solve the problem with optimal solution. Finally, the nonlinear problem was transformed to a linear programming problem with two constraints. No more conversion was made to the initial problem. Numerical examples were illustrated to show the efficiency of the method. In addition, the computer operation of the current algorithms was discussed by using MATLAB 2013a to solve a constructed numerical example.